2013
DOI: 10.4238/2013.september.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Assessment of clinical scoring systems for the diagnosis of Williams-Beuren syndrome

Abstract: ABSTRACT. Williams-Beuren syndrome (WBS) is a genetic disorder characterized by physical and intellectual developmental delay, associated with congenital heart disease and facial dysmorphism. WBS is caused by a microdeletion on chromosome 7 (7q11.23), which encompasses the elastin (ELN) gene and about 27 other genes. The gold standard for WBS laboratory diagnosis is FISH (fluorescence in situ hybridization), which is very costly. As a possible alternative, we investigated the accuracy of three clinical diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…45 In contrast, FISH allows for precise gene copy number determination in individual cells, rendering it independent from the purity of cancer tissues or presence of aneusomy. [46][47][48] 8p deletions were unevenly distributed between breast cancer subtypes, providing further support for the existence of biological differences between different subtypes of breast cancer. The higher rate of 8p deletions in NST as compared to lobular cancer is not surprising as most genomic alterations are more frequent in NST than in lobular carcinomas such as amplifications of HER2, 41,49 MYC, 41 MDM1, 41 and AIB1, 50 or overexpression of p53.…”
Section: Discussionmentioning
confidence: 92%
“…45 In contrast, FISH allows for precise gene copy number determination in individual cells, rendering it independent from the purity of cancer tissues or presence of aneusomy. [46][47][48] 8p deletions were unevenly distributed between breast cancer subtypes, providing further support for the existence of biological differences between different subtypes of breast cancer. The higher rate of 8p deletions in NST as compared to lobular cancer is not surprising as most genomic alterations are more frequent in NST than in lobular carcinomas such as amplifications of HER2, 41,49 MYC, 41 MDM1, 41 and AIB1, 50 or overexpression of p53.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of typical forms of WBS is 1:7500 live births, but the partial form is still poorly understood in developing countries. 1 , 2 To our knowledge, this is the first case reported in Burkina Faso.…”
Section: Discussionmentioning
confidence: 70%
“…Williams-Beuren syndrome (WBS), is a rare genetic neurodevelopmental disorder characterized by a set of somatic, psychological, and behavioral disorders. 1 , 2 Little is known about WBS in last developed and developing countries; this disease is under-diagnosed or diagnosed late, which causes several consequences on both somatic and psychological aspects. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Children with Williams Beuren syndrome have typical facial dysmorphy (elfin face), congenital cardiopathy and intellectual disability. The genetic basis of this syndrome has already been established, that is microdeletion of the 7 th chromosome (7q11.23) which encompass elastin and additionally 27 genes [7,8,9]. The pathophysiology and genetics of IIH had been confused for many decades until group from Muenster (Germany) published report in New England Journal of Medicine in 2011 and found that majority of patients with IIH had mutation CYP24A1 gene.…”
Section: Discussionmentioning
confidence: 99%